Analysis of CO2 Transfer in a Siphon-Mediated Bioreactor and Its Impact on the Fermentation Dynamics and Nutrient Profile of Sargassum-Based Biostimulants - Nurhayati, Nurhayati; Bhernama, Bhayu Gita; Bellia, Santi; Asmara , Anjar Purba (Elkawnie, 2026)
Abstract: Controlling gaseous byproducts such as CO2 during fermentation is crucial for optimising microbial activity and product consistency in biostimulant production. This study evaluates CO2 transfer dynamics in a siphon-mediated dual-tank fermentation system and its impact on pH regulation and Sargassum liquid fertiliser (SLF) nutrient composition. Two siphon diameters (1.5 cm and 0.5 cm denoted as I and II, respectively) were tested over 21 days, and a revised generation-limited physical model was developed to describe gas transport under low-pressure conditions. Cumulative CO2 transfer reached 250 ± 12 g (siphon I) and 205 ± 10 g (siphon II) (p < 0.01), with average volumetric flow rates of 7.8 × 10-5 and 6.3 × 10-5 L s-1, respectively. Estimated headspace pressures (18–35 Pa) confirmed laminar, near-atmospheric operation, indicating that gas transfer was biologically limited rather than hydraulically constrained. Increased CO2 transfer significantly reduced pH in the receiving tank (ΔpH up to −1.8; p < 0.01), demonstrating strong coupling between gas dissolution and acidification. Temperature (32–33 oC) and relative humidity (87–92%) showed moderate correlations with CO2 production (R2 = 0.65–0.76), suggesting environmentally modulated fermentation kinetics. Higher CO2 transfer enhanced total nitrogen content in SLF (up to 2.25 ± 0.14%; R2 = 0.92), while phosphorus and potassium exhibited nonlinear responses. Overall, the system functions as a biologically driven, low-pressure gas redistribution model, where the siphon diameter acts as a secondary parameter for optimising nutrient transformation, which can be applied to enhance the productivity of organic fertiliser industries.  Abstrak: Kontrol terhadap hasil samping gas CO2 selama fermentasi sangat penting untuk mengoptimalkan aktivitas mikroba dan konsistensi produk dalam produksi biostimulan. Studi ini mengevaluasi transfer CO2 dalam sistem fermentasi tangki ganda yang dihubungkan oleh sifon dan dampaknya terhadap pengaturan pH dan komposisi nutrisi pupuk cair (SLF). Dua diameter sifon (1,5 cm dan 0,5 cm, atau sifon I dan II) diuji selama 21 hari, dan model fisik terbatas generasi yang direvisi dikembangkan untuk menggambarkan transportasi gas dalam kondisi tekanan rendah. Transfer CO2 kumulatif mencapai 250 ± 12 g (sifon I) dan 205 ± 10 g (sifon II) (p < 0,01), dengan laju aliran volumetrik rata-rata masing-masing 7,8 × 10-5 dan 6,3 × 10-5 L s-1. Estimasi tekanan ujung (18–35 Pa) mengonfirmasi operasi laminar, mendekati atmosfer, menunjukkan bahwa transfer gas dibatasi secara biologis dan bukan secara hidraulik. Peningkatan transfer CO2 secara signifikan mengurangi pH di tangki penerima (ΔpH hingga −1,8; p < 0,01), menunjukkan keterkaitan yang kuat antara pelarutan gas dan pengasaman. Suhu (32–33 oC) dan kelembapan relatif (87–92%) menunjukkan korelasi sedang dengan produksi CO2 (R2 = 0,65–0,76), menunjukkan kinetika fermentasi yang dimodulasi oleh lingkungan. Transfer CO2 yang lebih tinggi meningkatkan kandungan N total dalam SLF (hingga 2,25 ± 0,14%; R2 = 0,92), sementara P dan K menunjukkan respons nonlinier. Secara keseluruhan, sistem ini berfungsi sebagai model redistribusi gas bertekanan rendah yang digerakkan secara biologis, di mana diameter sifon bertindak sebagai parameter sekunder untuk mengoptimalkan transformasi nutrisi sehingga meningkatkan produksi SLF di skala industri.